Future health of AYA survivors. Issue 2 (26th October 2018) - Burkart, Madelyn; Sanford, Stacy; Dinner, Shira; Sharp, Lisa; Kinahan, Karen
Abstract: Adolescent and young adult (AYA) oncology patients (ages 15–39) have been identified as a group with healthcare disparities including gaps and challenges in diagnosis, access to care, research, clinical trial participation, and cure rates. Like other patient groups with cancer or other chronic illnesses, disparities can lead to poor future health and outcomes, which is a well‐recognized concern within the AYA population. Cancer is the leading disease‐related cause of death in this age range. Numerous interested groups including the National Cancer Institute have met to address the research and cancer care needs of AYAs. This review highlights how these gaps in care during and after treatment can affect future health of this population of patients. Access to care, models of survivorship care, and lack of provider education are discussed. Survivorship care and use of guidelines, and promotion of psychosocial support and health behaviors during treatment and beyond are essential to optimizing future health of AYA patients.